1996
DOI: 10.1007/bf02245614
|View full text |Cite
|
Sign up to set email alerts
|

The time course of binding to striatal dopamine D2 receptors by the neuroleptic ziprasidone (CP-88,059-01) determined by positron emission tomography

Abstract: Positron emission tomography (PET) and 11C-raclopride were used to assess the time course of binding to central dopamine D2 receptors by the novel neuroleptic ziprasidone. In a third party blind study, six healthy male control subjects received a predose of 40 mg ziprasidone and were scanned at an interval of between 4 and 36 h post-dose. One additional subject was assigned to placebo predose and was scanned at 4 h post-dose. Binding potential (BP) was compared with that seen in the subject predosed with place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
45
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(50 citation statements)
references
References 26 publications
4
45
1
Order By: Relevance
“…All these studies have established a relationship between higher D2 occupancy and higher prolactin elevation (Nordstrom et al, 1992;Bench et al, 1996;Kapur et al, 2000). However, the precise level at which striatal occupancy begins has varied considerably from one drug to the other (Nordstrom et al, 1992;Bench et al, 1996;Kapur et al, 2000). Given the severalfold variation across antipsychotics with reference to their central to peripheral ratios shown here, it is not surprising that no absolute relationship between central occupancy and prolactin elevation has been or could logically be shown.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…All these studies have established a relationship between higher D2 occupancy and higher prolactin elevation (Nordstrom et al, 1992;Bench et al, 1996;Kapur et al, 2000). However, the precise level at which striatal occupancy begins has varied considerably from one drug to the other (Nordstrom et al, 1992;Bench et al, 1996;Kapur et al, 2000). Given the severalfold variation across antipsychotics with reference to their central to peripheral ratios shown here, it is not surprising that no absolute relationship between central occupancy and prolactin elevation has been or could logically be shown.…”
Section: Discussionmentioning
confidence: 72%
“…Nonetheless, several researchers have used striatal D2 occupancy as a proxy measure of pituitary occupancy and attempted to relate prolactin elevation to striatal D2 occupancy. All these studies have established a relationship between higher D2 occupancy and higher prolactin elevation (Nordstrom et al, 1992;Bench et al, 1996;Kapur et al, 2000). However, the precise level at which striatal occupancy begins has varied considerably from one drug to the other (Nordstrom et al, 1992;Bench et al, 1996;Kapur et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Previous PET studies have established that ziprasidone penetrates the brain at the dose used in this study: high levels of occupancy have been observed at both the D 2 receptor (Bench et al, 1996) and the 5-HT 2A receptor (Fischman et al, 1996) as discussed in the introduction. Flesinoxan penetrates the brain in rats, albeit much less efficiently than the prototypical 5-HT 1A receptor agonist 8-hydroxy-2-(di-n-propylamino)tetralin, 8-OH-DPAT (Hadrava et al, 1995).…”
Section: Discussionmentioning
confidence: 78%
“…The former effect is prevented and the latter roughly halved by the 5-HT 1A antagonist WAY-100635. In human PET studies, 40 mg oral ziprasidone occupies B72% D 2 receptors using the D 2 antagonist radiotracer [ 11 C]raclopride (Bench et al, 1996) and B95% 5-HT 2A receptors using the 5-HT 2A antagonist radioligand [ 18 F]setoperone (Fischman et al, 1996) 4-8 h post-dose. In patients with acute exacerbations of schizophrenia and schizoaffective disorder, randomized double-blind studies have shown ziprasidone to have efficacy superior to placebo (Daniel et al, 1999;Keck et al, 1998) and similar to haloperidol (Goff et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…In healthy volunteers, positron emission computed tomography (PET) studies confirmed that the occupancy by ziprasidone of 5HT 2 receptors substantially exceeded that of D 2 receptors (Fischman et al 1996;Bench et al 1993;Bench et al 1996). In a 28-day clinical trial in which the majority of patients (84/90) had an acute exacerbation of schizophrenia or schizoaffective disorder, ziprasidone 160 mg/day reduced Brief Psychiatric Rating Scale (BPRS) total and core item scores and Clinical Global Impression of Severity (CGI-S) scores similarly to haloperidol 15 mg/day (Goff et al 1998).…”
mentioning
confidence: 99%